Endovascular Aneurysm Repair Using Anaconda Repositionable Aortic Stent Graft Assisted Exclusively by Intravascular Ultrasound Imaging - Gaetano La Barbera (Radcliffe Medical Media, 2019)
Arteriography with contrast medium (CM) injection is normally employed to visualise the lowest renal artery during endovascular aneurysm repair (EVAR). Intravascular ultrasound (IVUS) has been proposed as an alternative, real-time imaging diagnostic technique to arteriography. In this study, we evaluated the feasibility of EVAR using Anaconda repositionable aortic stent graft (Vascutek) assisted by IVUS (Volcano Visions, Philips) during intraluminal navigation without CM. From January 2016 to December 2017, 25 patients with infrarenal abdominal aortic aneurysms, identified through anatomical inclusion criteria, underwent EVAR. All of the patients had an arteriogram at the end of the EVAR procedure to confirm aortic stent graft patency and to exclude type 1 endoleaks. The primary objective was the technical and clinical success of this CM-free aortic stent graft delivery procedure. At the end of the period, 150 target vessels were evaluated. IVUS versus angio-CT sensitivity and specificity rate were 97.3% and 100%, respectively. The primary technical success was obtained in 88% of the cases. Three patients (12%) needed CM injection to complete the procedure and there were no cases of type 1 endoleak. Primary clinical success was 100%. During follow-up at a mean of 20 months, none of the patients died or had complications. We conclude that a full EVAR procedure is feasible using only IVUS navigation and repositionable aortic stent graft without CM injection in anatomically selected cases.